2017
DOI: 10.1021/acs.jctc.7b00504
|View full text |Cite
|
Sign up to set email alerts
|

Protein–Ligand Dissociation Simulated by Parallel Cascade Selection Molecular Dynamics

Abstract: We investigated the dissociation process of tri-N-acetyl-d-glucosamine from hen egg white lysozyme using parallel cascade selection molecular dynamics (PaCS-MD), which comprises cycles of multiple unbiased MD simulations using a selection of MD snapshots as the initial structures for the next cycle. Dissociation was significantly accelerated by PaCS-MD, in which the probability of rare event occurrence toward dissociation was enhanced by the selection and rerandomization of the initial velocities. Although thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(112 citation statements)
references
References 77 publications
7
105
0
Order By: Relevance
“…This computational cost corresponds to a total simulation time of 40 ns (0.1 ns MD per replica × 400 cycles) and total computational cost of 400 ns (40 ns × 10 replicas). Relatively large variations in the number of PaCS-MD cycles required to cause the dissociation were consistent with the results of the earlier paper 31 , which showed that this number varied in different trials when SASA, Vex, cavity volume (Vcav), and also showed no significant change between the two pressure conditions (Table S1). It is worth mentioning that the TIP3P model 41 however, the amount of shrinkage was equivalent only to the size of one water molecule, which is smaller than the observed cavity and volume fluctuations.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This computational cost corresponds to a total simulation time of 40 ns (0.1 ns MD per replica × 400 cycles) and total computational cost of 400 ns (40 ns × 10 replicas). Relatively large variations in the number of PaCS-MD cycles required to cause the dissociation were consistent with the results of the earlier paper 31 , which showed that this number varied in different trials when SASA, Vex, cavity volume (Vcav), and also showed no significant change between the two pressure conditions (Table S1). It is worth mentioning that the TIP3P model 41 however, the amount of shrinkage was equivalent only to the size of one water molecule, which is smaller than the observed cavity and volume fluctuations.…”
Section: Resultssupporting
confidence: 89%
“…This showed that the free energy difference between the bound and unbound states significantly decreases as the pressure increases, which clearly indicates weaker binding affinity at higher pressure. Although only five PaCS-MD trials were conducted, the free energy profiles showed small standard deviations, indicating that free energy converges to a certain value independent of dissociation direction if two molecules are sufficiently separated and interactions between the molecules become negligibly small, as shown in earlier work 29,31 . It should be noted that the free energy converged upon complete detachment of the complex, shown by red triangles in Fig.…”
Section: Pressure Impairs Cheyp-flimn Bindingmentioning
confidence: 71%
See 1 more Smart Citation
“…PaCS-MD can simulate dissociation process of protein complexes, whose time scales range from μs to s, without using artificial forces within a short MD simulation time 29 . Additionally, by integrating the distributed MD trajectories using a Markov state model (MSM) 30 , various quantities characterizing molecular interactions can be calculated, such as binding free energy, association/dissociation rate constants, and residence times 29,31 .In the present study, we investigate the effect of high pressure on the interactions between the chemotaxis signaling protein CheY and the flagellar rotor protein FliM by a combination of MD, PaCS-MD/MSM, and high-pressure microscopy. Switching of the bacterial flagellar motor from counter-clockwise (CCW) to clockwise (CW) is triggered by the binding of the phosphorylated CheY (CheYp) to the N-terminal segment of FliM (FliM N ) 32,33 , which is essential for bacterial chemotaxis 34 .…”
mentioning
confidence: 99%
“…However, ligand binding/unbinding processes can be excessively longer than microsecond simulation lengths by using computer hardware available to most scientists [13][14][15] . Various methods such as aMD, metadynamics, weighted ensemble, scale-MD, and PaCS-MD have been used to accelerate sampling the ligand binding/unbinding processes [16][17][18][19][20][21][22][23][24][25][26][27] . In terms of the binding paths found, various algorithms such as umbrella sampling 28,29 and milestoning [30][31][32][33] have been used to estimate kinetic rates and free energy profile.…”
Section: Introductionmentioning
confidence: 99%